FENOMENA DIGITAL ERA REVOLUSI INDUSTRI 4.0 - Farid Abdullah (Universitas Trisakti, 2019)
Abstract Digital Phenomena in Industrial Revolution 4.0. Entering the era of Industrial Revolution 4.0, the Indonesian government set up a roadmap in the form of Making Indonesia 4.0. To support the digital phenomenon, this article is strengthened by public lecture Eric Hanson CEO of xRez Studio Inc. Greater Los Angeles, USA, on February 5, 2018 themed “Creating Digital Cities”. As a designer, visual effects senior producer,and 3-dimensional digital artist he has been in the production of visual effects-based films in Holywood. The arrival of Hanson made an important contribution to Visual Communication and Multimedia Design education in Indonesia. Visual communication design paradigm according to Hanson experiencing a media shifting. Many works of art, multi media, prints, previously leaning on consumables, shifted to E-media. The existence of this e-media is difficult to resist and many of the efficiency it produces.Hanson also explained his arrival as a form of introduction to the younger generation the opportunities of work in the field of visual communication design.AbstrakFenomena Digital Era Revolusi Industri 4.0. Memasuki era Revolusi Industri 4.0, pemerintah Indonesia menyusun peta jalan berupa Making Indonesia 4.0. Untuk mendukung fenomena digital tersebut, tulisan ini diperkuat kuliah umum Eric Hanson, CEO xRez Studio Inc. Greater Los Angeles, USA, bertema “Creating Digital Cities”.Pendekatan yang dipakai dalam tulisan ini adalah deskriptif-naratif, memakai teori Rogers E. Shoemaker (1995) difusi teknologi komputer terhadap komunitas seni. Fenomena desain komunikasi visual menurut Hanson mengalami perubahan media (media shifting). Banyak karya seni, multimedia, cetakan, yang sebelumnya bersandar pada bahan habis, bergeser pada e-media. Keberadaan e-media ini sulit ditolak dan banyak efisiensi yang dihasilkannya. Simpulan dari tulisan ini adalah telah terjadi fenomena digitalisasi di berbagai kota-kota dunia dan perlunya introduksi kepada generasi muda tanah air terhadap peluang-peluang kerja di bidang desain